Langkah Kreatif: Pojok Baca Kelas Sebagai Sarana Menumbuhkan Minat Baca di MI Al-Khoiriyyah 2 Semarang - Taufik Hidayat; Musyid Musyid (Universitas Muhammadiyah Bandung, 2024)
It is difficult for the reading culture in Indonesia to thrive. There are many factors that cause this. One of them is the lack of effort in cultivating a reading culture as early as possible. This is quite worrying because it will have implications for the quality of human resources decreasing. This research aims to analyze the role of reading corner media in fostering a reading culture in basic education institutions. This research uses descriptive qualitative research methods with case studies at MI Al-Khoiriyyah 2 Semarang in grades 5 and 6. Data collection techniques use participatory observation, interviews and documentation techniques. The results of this research show that the reading corner media found in every corner of the classroom is quite effective in fostering a reading culture among students. Through reading, students are encouraged to imagine and think in simple terms. However, there are also several challenges that must be faced, such as the rise of online games, lack of parental example at home and school facilities and infrastructure. It is hoped that this article will be able to raise the awareness of various related parties to actively participate in efforts to build a reading culture in Indonesia, starting from childhood.